Semiconductor heat treatment member

By fusing quartz glass members with controlled devitrification and specific elemental content, the semiconductor heat treatment member addresses integration challenges and maintains strength, suitable for semiconductor processing.

JP2025009902APending Publication Date: 2025-01-20COORSTEK GK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024093315
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-07
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

The integration of quartz glass plates in semiconductor heat treatment members is challenging due to the risk of bubble formation and cracking during welding, and devitrification occurs during fusion bonding, leading to strength reduction and opacity.

Method used

The semiconductor heat treatment member is constructed by fusing quartz glass members with controlled devitrification, limiting the maximum cross-sectional area of devitrification to 1.76 mm² and area ratio to 10% or less, and maintaining specific elemental content within 5-25 ppm Al, 2.0 ppm Ca, 0.3 ppm Mg, and 0.5 ppm Na, while applying pressure between 0.1-10 kg/cm² at 1000-1700°C.

Benefits of technology

This approach suppresses significant strength reduction and maintains structural integrity, ensuring suitable performance for semiconductor processing by minimizing devitrification and thermal deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009902000001_ABST
    Figure 2025009902000001_ABST
Patent Text Reader

Abstract

To provide a semiconductor heat treatment member that can be used suitably for semiconductor heat treatment by suppressing significant strength loss due to permeation loss.SOLUTION: A semiconductor heat treatment member according to the present invention is a semiconductor heat treatment member made of quartz, a plurality of perforation areas are formed in the fusion bonded area where the quartz glass member is fused, the maximum cross-sectional area of one of a plurality of perforations is less than 1.76 mm2, and the area occupancy of the total area of the plurality of perforation areas in relation to the area of the cross-section of the fusion bonded area is 10% or less.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a semiconductor heat treatment member, and more particularly to a semiconductor heat treatment member formed by fusing a plurality of quartz glass members together. [Background technology]

[0002] When manufacturing a box-shaped chamber (semiconductor heat treatment member) for processing semiconductor wafers and the like from quartz glass, it is not easy to mold it as a single unit. For this reason, a method has been proposed in which the ends of a plurality of quartz glass plates are connected by heat welding. For example, Patent Document 1 discloses a method for producing a heat treatment container for processing semiconductor wafers, etc., in which the ends of multiple quartz glass plates to be connected that form the walls, etc. are heated and welded together using an oxygen-hydrogen burner, etc., and assembled into a box shape.

[0003] However, when quartz glass plates are connected to each other by welding, there is a risk that bubbles may be trapped in the welded portion, reducing its strength, and there is a problem in that the welded portion is prone to cracking.

[0004] As a method for connecting quartz glass plates that solves the problems associated with welding, there is a method called fusion (welding). For example, when connecting the ends of two quartz glass plates, the ends are heated to a high temperature just before melting. According to such a connection method by fusion, it is possible to connect quartz glass members together without the risk of bubbles being mixed into the welded portion, which would reduce the strength of the connection as occurs with welding. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 10-178005 Summary of the Invention [Problem to be solved by the invention]

[0006] When quartz glass members are fused together, white spots called devitrification tend to occur in the material and at the fused interface. This devitrification occurs when crystallization progresses from a metastable glass state to an aggregate of crystal grains that grow from many crystal nuclei. As a result, the devitrified areas become opaque because the grain boundaries of the crystals scatter light. Also, since devitrification can be the starting point for product destruction due to a decrease in strength, it is generally considered preferable to remove it.

[0007] However, it is difficult to perform fusion bonding completely free of devitrification, and it is more realistic to minimize devitrification by low-temperature fusion. That is, if it is possible to reduce the devitrification occurring in the fusion bonded portion while preventing an extreme decrease in strength even if devitrification is present, it can be used as a semiconductor heat treatment member.

[0008] The inventors of the present invention therefore conducted extensive research into the range of devitrification in which the strength does not decrease significantly even if devitrification occurs, and discovered that if the occurrence of devitrification is within a predetermined range, a significant decrease in strength is suppressed and the glass can be suitably used as a semiconductor heat treatment member, and thus completed the present invention.

[0009] The present invention has been made under the above circumstances, and aims to provide a semiconductor heat treatment component having a fusion part in which quartz glass members are fused together, in which a significant decrease in strength due to devitrification is suppressed and which can be suitably used for semiconductor heat treatment. [Means for solving the problem]

[0010] The semiconductor heat treatment member according to the present invention, which has been made to solve the above problems, is a semiconductor heat treatment member formed by fusing a plurality of quartz glass members together, wherein a plurality of devitrified portions are formed in a fusion portion where the quartz glass members are fused together, and the maximum cross-sectional area of ​​any one of the plurality of devitrified portions is 1.76 mm 2or less, and the area occupancy rate of the total area of ​​the plurality of devitrified portions relative to the cross-sectional area of ​​the fused portion is 10% or less.

[0011] Here, the volume occupancy rate per unit volume of the devitrified portion in the wall other than the fused portion is desirably 0.015% or less. Moreover, it is preferable that the quartz glass member has an Al content of 5 ppm by weight or more and 25 ppm by weight or less.

[0012] In this way, the semiconductor heat treatment member of the present invention is a semiconductor heat treatment member made of quartz, in which a plurality of devitrified portions are formed in a fusion portion where a quartz glass member is fused, and the maximum cross-sectional area of ​​any one of the plurality of devitrified portions is 1.76 mm 2 Hereinafter, the area occupancy rate of the total devitrified portion relative to the cross-sectional area of ​​the fusion portion is set to 10% or less. The semiconductor heat treatment member according to the present invention having this configuration is suppressed from being significantly reduced in strength, and can be suitably used for semiconductor heat treatment. Effect of the Invention

[0013] According to the present invention, even if the fused portion of the fused semiconductor heat treatment member contains devitrification (devitrification portion), so long as the devitrification is within a predetermined range, a significant decrease in strength due to devitrification can be suppressed, and the semiconductor heat treatment member can be suitably used for semiconductor processing. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a perspective view of a semiconductor heat treatment member according to the present invention. [Diagram 2] FIG. 2(a) is an enlarged front view of a portion of the semiconductor heat treatment member of FIG. 1, and FIG. 2(b) is a plan view of FIG. 2(a). [Diagram 3] FIG. 3 is a conceptual diagram for explaining a method for measuring breaking strength by a three-point bending test. [Figure 4] FIG. 4 is a conceptual diagram for explaining a method for evaluating thermal deformation by calculating the amount of deformation from the length of a quartz glass plate before and after fusion. [Diagram 5] FIG. 5 is a conceptual diagram showing a plurality of devitrified parts formed in the fusion bonded part. [Figure 6] FIG. 6 is a conceptual diagram showing a plurality of devitrified parts formed in the wall other than the fused part. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, one embodiment of a semiconductor heat treatment member according to the present invention will be described with reference to FIGS. FIG. 1 is an oblique view showing a portion of a chamber as a semiconductor heat treatment member of the present invention, FIG. 2(a) is a front view showing an enlarged portion of the semiconductor heat treatment member of FIG. 1 (the portion surrounded by the dashed line in FIG. 1), and FIG. 2(b) is a plan view of FIG. 2(a) and an enlarged plan view of a portion of the semiconductor heat treatment member of FIG. 1. It should be noted that the drawings are schematic or conceptual, and the relationship between the thickness and width of each portion, the size ratio between portions, etc. are not accurately illustrated.

[0016] As shown in FIG. 1, a chamber 1 (semiconductor heat treatment member) is constructed by assembling a plurality (five in the figure) of rectangular quartz glass plates 2 (quartz glass members) having a predetermined thickness. In the illustrated example, two side plates 2a and 2b made of quartz glass, one top plate 2c, one bottom plate 2d, and one back plate 2e are connected together to form the chamber 1. That is, in this example, the chamber 1 is formed into a box-like body with an opening at the front.

[0017] The ends (end faces or edges) of each of the quartz glass plates 2 are fusion-bonded. Specifically, the quartz glass plates 2 are heated and fused together while applying a predetermined pressure to the ends of the quartz glass plates 2. This causes devitrification in the fused portion F and in the parts other than the fused portion F, as shown in Figures 2(a) and (b). Here, the fused portion F refers to the interface between two fused and joined quartz glass plates 2. The inside of the quartz glass plate 2 other than the fused portion F refers to the inside of the quartz glass plate 2, excluding the outer surface, in the portion of the quartz glass plate 2 other than the fused portion F (interface).

[0018] Then, devitrification occurs in the fused portion F, as shown in Fig. 5. The devitrification occurring in the fused portion F has a linear or planar shape, and the fused portion F has a plurality of linear or planar devitrifications. Here, each devitrification is referred to as a devitrification portion X, and each devitrification portion X is illustrated in Fig. 5. Note that Fig. 5 is a schematic or conceptual drawing for easy understanding, and does not accurately illustrate the size of the devitrification portion X, etc.

[0019] In the fusion joint F, the devitrified portion X is planar or linear, and the maximum cross-sectional area of ​​one of the devitrified portions X is 1.76 mm 2 The total area of ​​all the devitrified portions X (total area occupancy rate) is 10% or less with respect to the cross-sectional area of ​​the fused portion F. The maximum cross-sectional area of ​​one of the devitrified parts X in the fusion part F is 1.76 mm 2 If it exceeds this value, the strength decreases, which is not preferable. Furthermore, if the total area of ​​all the devitrified portions X (total area occupancy rate) exceeds 10% of the cross-sectional area of ​​the fused portion F, the strength also decreases, which is not preferable. Here, the maximum cross-sectional area of ​​the devitrified portion X refers to a cross section of the devitrified portion cut at any angle, and the cross section at any angle satisfies the above range. Also, the cross-sectional area of ​​the fused portion F refers to a cross section of the fused portion F cut along the fusion interface.

[0020] 6, a plurality of spherical devitrifications occur in the wall other than the fused portion F. This devitrification occurs when the fused portion F is formed. Here, each devitrification is referred to as a devitrification portion Y. Each devitrification portion Y is illustrated in Fig. 6. Note that Fig. 6 is a schematic or conceptual diagram for facilitating understanding, and does not accurately illustrate the size of the devitrification portion Y, etc. In one embodiment of the semiconductor heat treatment member according to the present invention, in the wall other than the fusion portion F, 5 or less spherical devitrified portions Y having an average diameter of 2 mm or more, 10 or less devitrified portions Y having an average diameter of 1 mm or more but less than 2 mm, and 15,000 or less devitrified portions Y having an average diameter of less than 1 mm are formed. When the devitrified portions Y present in the wall other than the fused portions F have the above distribution, a decrease in strength can be suppressed.

[0021] In addition, in the wall other than the fused portion F, the devitrified portions Y are spherical, and the volume occupancy rate of the total volume of the devitrified portions Y per unit volume is preferably 0.015% or less. By making the volume occupancy rate of the total volume of the devitrified portion Y in the wall other than the fused portion F 0.015% or less, it is possible to suppress a decrease in strength and further to suppress deformation due to heat.

[0022] In this semiconductor heat treatment member, the Al content is preferably 5 ppm by weight or more and 25 ppm by weight or less. By keeping the Al content in the above range, a decrease in strength can be suppressed. It is further preferable that the Ca content is 2.0 ppm by weight or less, the Mg content is 0.3 ppm by weight or less, and the Na content is 0.5 ppm by weight or less. By keeping the Ca content and the like within the above ranges, a decrease in strength can be suppressed.

[0023] Next, a method for manufacturing the chamber 1 as a semiconductor heat treatment member will be described. First, five quartz glass plates 2 (side plates 2a, 2b, top plate 2c, bottom plate 2d, and back plate 2e) constituting a chamber 1 that is a semiconductor heat treatment member are prepared. The quartz glass plate 2 has an Al content of 5 ppm by weight to 25 ppm by weight, a Ca content of 2.0 ppm by weight or less, a Mg content of 0.3 ppm by weight or less, and a Na content of 0.5 ppm by weight or less. A commercially available quartz glass plate may be used as long as the Al content is within the above range.

[0024] Next, the quartz glass plate 2 is heated to 1000° C. or more and 1700° C. or less, and subjected to a pressure of 0.1 kg / cm 2More than 10kg / cm 2 The ends are then pressed in opposing directions to be fused together.

[0025] 1, for example, the left and right edges of the bottom plate 2d are fused to the lower end faces of the side plates 2a and 2b, the upper end faces of the side plates 2a and 2b are fused to the left and right edges of the top plate 2c, and the rear end faces of the side plates 2a and 2b, the bottom plate 2d, and the top plate 2c are fused to the four edges of the back plate 2e. In this manner, the ends of all of the quartz glass plates 2 are connected to each other and cooled, thereby obtaining a chamber 1 (semiconductor heat treatment member) having the shape shown in FIG.

[0026] As described above, according to the present invention, when connecting the quartz glass plates 2 to each other, the quartz glass plates 2 are heated to 1000°C or more and 1700°C or less, and fused under pressure. If the temperature is less than 1000°C, the fused plates are not fused sufficiently due to the low temperature, resulting in a decrease in strength. If the temperature is more than 1700°C, the shape of the quartz glass plates 2 cannot be maintained due to the high temperature. The pressure during welding is 0.1kg / cm 2 More than 10kg / cm 2 It is desirable to press the ends in opposing directions below. 0.1kg / cm 2 More than 10kg / cm 2 By applying pressure below this level, the quartz glass plate 2 can be fused without deforming it. Also, the edge of the quartz glass plate 2 can be fused uniformly.

[0027] In the fused portion F where the quartz glass plate 2 is fused, the devitrified portion X is planar or linear, and the maximum cross-sectional area of ​​one of the devitrified portions X is 1.76 mm 2 The total area (occupancy rate) of all the devitrified portions X is 10% or less of the cross-sectional area of ​​the fused portion F. The maximum cross-sectional area of ​​one of the devitrified portions X and the total area of ​​all the devitrified portions X (area occupancy rate) are controlled by the degree of pressure, the heating temperature of the quartz glass plate 2, or the Al content of the quartz glass member.

[0028] In the above embodiment, a chamber 1 formed by fusing multiple quartz glass plates is shown as a semiconductor heat treatment component according to the present invention, but the present invention is not limited to this form and can be widely applied to semiconductor heat treatment components formed by fusing quartz glass components together. EXAMPLES

[0029] The semiconductor heat treatment member and the manufacturing method thereof according to the present invention will be further described with reference to examples.

[0030] [experiment] In the experiment, the maximum cross-sectional area (mm 2 ), the total area of ​​all devitrified areas relative to the cross-sectional area of ​​fused portion F (area occupancy %), and the volume occupancy % of devitrified areas other than fused portion F were examined.

[0031] Example 1 In Example 1, two quartz glass plates (Al: 10 ppm by weight, Ca: 1.0 ppm by weight, Mg: 0.1 ppm by weight, Na: 0.1 ppm by weight) were prepared. The length of the quartz glass plate was 100 mm, the width was 100 mm, and the thickness was 30 mm, and two quartz glass plates of the same dimensions were prepared. No devitrification was observed in the two quartz glass plates. The content of each element in the quartz glass plate was measured using ICP emission spectrometry.

[0032] Then, the ends of the two quartz glass plates are heated, and when they reach 1700°C, a pressure of 5 kg / cm 2 The ends were fused together at 400 rpm for 1 hour to prepare a sample. As shown in Figure 3, a load was applied to the fused portion of the obtained sample, and the breaking strength was measured and evaluated by a three-point bending test (JIS1601:2008). As a result, the breaking strength was 135 MPa or more, which is good in terms of strength, and is recorded as ○ in Table 1. In Table 1, since the breaking strength of the quartz glass member itself was 135 MPa, breaking strengths of 135 MPa or more were marked as O because they were greater than the breaking strength of the quartz glass itself, and breaking strengths of less than 135 MPa were marked as × because they were smaller than the breaking strength of the quartz glass itself.

[0033] In addition, as shown in Figure 4, the length (measured with a vernier caliper) before and after fusion in the direction perpendicular to the pressure direction during fusion of the quartz glass plate was compared to calculate the amount of deformation, and the thermal deformation was evaluated. As a result, the amount of deformation was 2.5 mm, which was small and good, and was recorded as ○ in Table 1. In Table 1, the deformation amount is expressed as ◯ when it is 0 to 3.0 mm, and as △ when it is more than 3.0 mm.

[0034] 5, the area of ​​one devitrified portion X having the largest area among the devitrified portions X in the fusion portion was measured using a microscope. The area occupancy rate (%) of the total area of ​​the devitrified portions relative to the area of ​​the fusion portion was also measured. As a result, the area of ​​one devitrified portion X having the largest area among the devitrified portions X was 1.62 mm 2 The area occupancy rate (%) of the total area of ​​the devitrified portions relative to the area of ​​the fused portions was 9%. In addition, the volume occupancy (%) of the total volume of the devitrified portion Y per unit volume was measured in the specimen by microscope and visual observation as shown in Fig. 6. As a result, the volume occupancy (%) of the devitrified portion Y was 0.015%.

[0035] Example 2 In Example 2, quartz glass plates (Al: 18 ppm by weight, Ca: 1.0 ppm by weight, Mg: 0.1 ppm by weight, Na: 0.1 ppm by weight) were used. No devitrification was observed in the two quartz glass plates. The content of each element in the quartz glass plates was measured using ICP emission spectrometry. Then, the ends of the two quartz glass plates are heated, and when they reach 1300°C, a pressure of 5 kg / cm 2 The ends were fused together by applying pressure at 400 rpm for 1 hour to prepare a sample. The fused portions of the obtained samples were subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0036] Example 3 In Example 3, quartz glass plates (Al: 5 ppm by weight, Ca: 1.0 ppm by weight, Mg: 0.1 ppm by weight, Na: 0.1 ppm by weight) were used. No devitrification was observed in the two quartz glass plates. The content of each element in the quartz glass plates was measured using ICP emission spectrometry. Then, the ends of the two quartz glass plates are heated, and when they reach 1300°C, a pressure of 10 kg / cm 2 The ends were fused together by applying pressure at 400 rpm for 1 hour to prepare a sample. The fused portions of the obtained samples were subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0037] Example 4 In Example 4, quartz glass plates (Al: 25 ppm by weight, Ca: 1.0 ppm by weight, Mg: 0.1 ppm by weight, Na: 0.1 ppm by weight) were used. No devitrification was observed in the two quartz glass plates. The content of each element in the quartz glass plates was measured using ICP emission spectrometry. Then, the ends of the two quartz glass plates are heated, and when they reach 1700°C, a pressure of 10 kg / cm 2 The ends were fused together by applying pressure at 400 rpm for 1 hour to prepare a sample. The fused portions of the obtained samples were subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0038] Comparative Example 1 In Comparative Example 1, a quartz glass plate (Al: 26 ppm by weight, Ca: 1.0 ppm by weight, Mg: 0.1 ppm by weight, Na: 0.1 ppm by weight) was used. No devitrification was observed in the two quartz glass plates. The content of each element in the quartz glass plate was measured using ICP emission spectrometry. The ends of the two quartz glass plates were then heated at 1700°C for 1 hour and subjected to a pressure of 0.01 kg / cm 2The ends were fused together by applying pressure at 400 rpm for 1 hour to prepare a sample. The fused portions of the obtained samples were subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0039] Comparative Example 2 In Comparative Example 2, the quartz glass plates used in Example 1 were used, and the ends of the two quartz glass plates were heated at 1700° C. for 1 hour and 0.01 kg / cm 2 The ends were fused together by applying pressure at 400 rpm for 1 hour to prepare a sample. The fused portions of the obtained samples were subjected to the same measurements and evaluations as in Example 1. The results are shown in Table 1.

[0040] Comparative Example 3 In Comparative Example 3, the quartz glass plates used in Example 1 were used, and the ends of the two quartz glass plates were heated at 1800° C. and 5 kg / cm 2 After applying pressure for one hour, the quartz glass plate was no longer able to maintain its shape, and it was no longer possible to prepare a sample.

[0041] Comparative Example 4 In Comparative Example 4, the quartz glass plates used in Example 1 were used, and the ends of the two quartz glass plates were heated to 900° C. and 5 kg / cm 2 After applying pressure for an hour, it did not fuse.

[0042] The results of Examples 1 to 4 and Comparative Examples 1 and 2, excluding Comparative Examples 3 and 4, are shown in Table 1. As described above, in the evaluation 1 (breaking strength) in Table 1, ◯ indicates a breaking strength of 135 MPa or more, and × indicates a breaking strength of less than 135 MPa. In addition, in the evaluation 2 (thermal deformation), ◯ indicates a deformation amount of 0 to 3.0 mm, and △ indicates a deformation amount of more than 3.0 mm.

[0043] [Table 1]

[0044] As shown in Table 1, in order to secure the necessary fracture strength and sufficiently suppress thermal deformation, the maximum cross-sectional area of ​​one devitrification in the fusion joint must be 1.76 mm 2 It was confirmed that the area occupancy rate of the total area of ​​the devitrified portions was 10% or less. [Explanation of symbols]

[0045] 1. Chamber (semiconductor heat treatment components) 2 Quartz glass plate (quartz glass component) 2a side plate 2b side plate 2c Top plate 2d bottom plate 2e backboard F fusion part X Devitrification Y devitrification

Claims

1. A semiconductor heat treatment member formed by fusing a plurality of quartz glass members together, a plurality of devitrified portions are formed in the fused portion where the silica glass member is fused; The maximum cross-sectional area of ​​one of the plurality of devitrification portions is 1.76 mm 2 is as follows: A semiconductor heat treatment member, characterized in that the total area of ​​the plurality of devitrified portions is 10% or less of the cross-sectional area of ​​the fusion bonded portion.

2. 2. The semiconductor heat treatment member according to claim 1, wherein the volume occupancy rate per unit volume of the devitrified portion in the wall other than the fused portion is 0.015% or less.

3. The quartz glass member has an Al content of 5 ppm by weight or more and 25 ppm by weight or less.

Citation Information

Patent Citations

  • Method for molding quartz glass

    JP1996151220A

  • Quartz glass for heat-treating jig for silicon semiconductor element

    JP1996165134A

  • Welding of silica glass member

    JP1999060257A

  • Microchip and its manufacturing method

    JP2007170958A

  • Thin piece treating and heat treatment device

    JP1998178005A